2014
DOI: 10.1111/jdv.12799
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP3 and IL12B gene polymorphisms associated with psoriasis vulgaris in an Egyptian cohort

Abstract: Replicating the association of single-nucleotide polymorphisms in the TNFAIP3, IL12B and IL23R genes with psoriasis vulgaris, in subjects from different ethnic backgrounds, underlines their importance in the pathogenesis of the disease. In contrast, the lack of any association between rs20541 (IL13) and psoriasis in our Egyptian cohort suggests the existence of important inter-ethnic genetic differences in psoriasis susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In our study, no signal was detected within the IL23R and IL12B genes as it was published in previous findings by Haase et al . This can be explained that the statistical power in our study estimates variant with odds ratio of 2 or more with a 80% probability; however, the odds ratio of the non‐replicated finding is lower justifying why they did not achieve significance such as IL23R variant rs9988642 that has an odds ratio of 1.4 .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, no signal was detected within the IL23R and IL12B genes as it was published in previous findings by Haase et al . This can be explained that the statistical power in our study estimates variant with odds ratio of 2 or more with a 80% probability; however, the odds ratio of the non‐replicated finding is lower justifying why they did not achieve significance such as IL23R variant rs9988642 that has an odds ratio of 1.4 .…”
Section: Resultssupporting
confidence: 58%
“…To date, there has been no published GWAS or sequencing‐based association studies on the Egyptian population apart from an association study of four SNPs (rs610604 [ TNFAIP3 ], rs3212227 [ IL12B ], rs11209026 [ IL23R ] and rs20541 [ IL13 ]) with psoriasis performed on a cohort of restricted sample size . The aim of this study was to perform the first comprehensive GWAS in an Egyptian population, identifying population specific psoriasis susceptibility loci.…”
Section: Questions Addressedmentioning
confidence: 99%
“…Keratinocyte-specific deletion of A20 results in epidermal hyperproliferation and ectodermal defects, but skin infiltration of immune cells has not been observed (Lippens et al, 2011). Genome-wide association studies identified TNFAIP3/A20 as a susceptibility locus for psoriasis (Haase et al, 2015;Indhumathi et al, 2015;Li et al, 2014;Nair et al, 2009;and Zhang et al, 2015), and its role as a negative regulator in Th2-associated lung inflammation, in particular through its expression by dendritic cells, has been well characterized (Schuijs et al, 2015;Vroman et al, 2018). On the other hand, some cases of A20 haploinsufficiency yield distinct autoinflammatory and/or autoimmune skin pathology, possibly with skin ulcerations and pustular abscesses (Kadowaki et al, 2017;Takagi et al, 2017;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 13 articles, 11 articles containing original data for rs610604. These studies were performed in UK [19], Egypt [20], India [21], China [22][23][24][25], Pakistani [26], USA [27], Sweden [28], México [29]. In all, these studies included 11,556 psoriasis patients and 16,720 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%